Machine Learning Methods Performance Evaluation* - et. al., Zakoldaev D. A., (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we describe an approach for air pollution modeling in the data incompleteness scenarios, when the sensors cover the monitoring area only partially. The fundamental calculus and metrics of using machine learning modeling algorithms are presented. Moreover, the assessing indicators and metrics for machine learning methods performance evaluation are described. Based on the conducted analysis, conclusions on the most appropriate evaluation approaches are made.